Peptide Model of the Mutant Proinsulin Syndrome. II. Nascent Structure and Biological Implications - Yang, Yanwu; Glidden, Michael D.; Dhayalan, Balamurugan; Zaykov, Alexander N.; Chen, Yen-Shan; Wickramasinghe, Nalinda P.; DiMarchi, Richard D.; Weiss, Michael A. (Frontiers in Endocrinology, 2022)
Toxic misfolding of proinsulin variants in β-cells defines a monogenic diabetes syndrome, designated mutant INS-gene induced diabetes of the young (MIDY). In our first study (previous article in this issue), we described a one-disulfide peptide model of a proinsulin folding intermediate and its use to study such variants. The mutations (LeuB15 to Pro, LeuA16 to Pro, and PheB24 to Ser) probe residues conserved among vertebrate insulins. In this companion study, we describe 1H and 1H-13C NMR studies of the peptides; key NMR resonance assignments were verified by synthetic 13C-labeling. Parent spectra retain nativelike features in the neighborhood of the single disulfide bridge (cystine B19-A20), including secondary NMR chemical shifts and nonlocal nuclear Overhauser effects. This partial fold engages wild-type side chains LeuB15, LeuA16 and PheB24 at the nexus of nativelike alpha-helices alpha1 and alpha3 (as defined in native proinsulin) and flanking beta-strand (residues B24-B26). The variant peptides exhibit successive structural perturbations in order: parent (most organized) > SerB24 >> ProA16 > ProB15 (least organized). The same order pertains to (a) overall alpha-helix content as probed by circular dichroism, (b) synthetic yields of corresponding three-disulfide insulin analogs, and (c) ER stress induced in cell culture by corresponding mutant proinsulins. These findings suggest that this and related peptide models will provide a general platform for classification of MIDY mutations based on molecular mechanisms by which nascent disulfide pairing is impaired. We propose that the syndrome’s variable phenotypic spectrum—onsets ranging from the neonatal period to later in childhood or adolescence—reflects structural features of respective folding intermediates.